The Use of Role-Playing Learning Model to Improve Critical Thinking Skills in IPAS Learning at Fourth Grade Elementary School - Annisa Rosma Fitriya; Ella Rahma Nura Aziza; Diah Septiningrum; Awanda Nurlailita Mahmudah; Dewi Afrianti; Habi Nugroho; Ira Eko Retnosar; Sri Kis Untari (EDUJAVARE: International Journal of Educational Research, 2026)
The rapid transformation of the twenty-first century has brought significant changes to the demands placed on education systems worldwide. This study aims to improve fourth-grade students’ critical thinking skills through the implementation of the role-playing learning model in IPAS learning at SDN Margorejo 1/403 Surabaya. The research employed a Classroom Action Research (CAR) design consisting of two stages: pre-cycle and Cycle I, following the procedures of planning, acting, observing, and reflecting. The subjects of the study were 25 fourth-grade students. Data were collected through observation, tests, and documentation, and analyzed using descriptive quantitative and qualitative techniques. The findings revealed a significant improvement in students’ learning outcomes and critical thinking skills. In the pre-cycle, the average formative score was 81.32, while the summative score was 74.40, with only 60% of students achieving the minimum mastery criterion. After the implementation of the role-playing model, the average formative score increased to 91.88 and the summative score to 89.92, with 100% of students achieving mastery. The results indicate that role-playing fosters active participation, collaboration, and contextual understanding, which contribute to the development of critical thinking skills. Therefore, the role-playing learning model is effective in enhancing students’ critical thinking in elementary IPAS learning.